2023
DOI: 10.31223/x52938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Defense of Metrics: Metrics Sufficiently Encode Typical Human Preferences Regarding Hydrological Model Performance

Abstract: Building accurate rainfall-runoff models is an integral part of hydrological science and practice. The variety of modeling goals and applications have led to a large suite of evaluation metrics for these models. Yet, hydrologists still put considerable trust into visual judgment, although it is unclear whether such judgment agrees or disagrees with existing quantitative metrics. In this study, we tasked 622 experts to compare and judge more than 14,000 pairs of hydrographs from 13 different models. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The collected responses as well as the code to generate all results and tables in this manuscript are publicly available at https://doi.org/10.5281/zenodo.7640347 (Gauch et al, 2023) for others to conduct additional analyses in future work. The hydrographs from the GRIP-GL study are available at https://doi.org/10.20383/103.0598 (see package "A5" for observations and package "A7" for modeled streamflow; Mai et al, 2022a).…”
Section: Appendix B: Classification Metricsmentioning
confidence: 99%
“…The collected responses as well as the code to generate all results and tables in this manuscript are publicly available at https://doi.org/10.5281/zenodo.7640347 (Gauch et al, 2023) for others to conduct additional analyses in future work. The hydrographs from the GRIP-GL study are available at https://doi.org/10.20383/103.0598 (see package "A5" for observations and package "A7" for modeled streamflow; Mai et al, 2022a).…”
Section: Appendix B: Classification Metricsmentioning
confidence: 99%
“…I have, of course, argued for a long, long time that the idea of an optimum hydrological model should be considered as untenable in favour of a concept of equifinality of models and parameter sets (e.g., Beven, 2006; Beven & Freer, 2001). Others have also suggested that the use of multiple metrics can reflect subjective judgements about the acceptability of different models (e.g., Gauch et al, 2022), though different experts might vary in their rankings (Crochemore et al, 2015).…”
Section: On Benchmarking and Intercomparisons Of Hydrological Modelsmentioning
confidence: 99%
“…Others have also suggested that the use of multiple metrics can reflect subjective judgements about the acceptability of different models (e.g., Gauch et al, 2022), though different experts might vary in their rankings (Crochemore et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also suggested that the use of multiple metrics can reflect subjective judgments about the acceptability of different models (e.g. Gauch et al, 2022), though different experts might vary in their rankings (Crochemore et al, 2015).…”
mentioning
confidence: 99%